2015
DOI: 10.1007/s00408-015-9831-6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Malignant Pleural Effusion by A Cancer Ratio (Serum LDH: Pleural Fluid ADA Ratio)

Abstract: AimWe studied the diagnostic potential of serum lactate dehydrogenase (LDH) in malignant pleural effusion.MethodsRetrospective analysis of patients hospitalized with exudative pleural effusion in 2013.ResultsSerum LDH and serum LDH: pleural fluid ADA ratio was significantly higher in cancer patients presenting with exudative pleural effusion. In multivariate logistic regression analysis, pleural fluid ADA was negatively correlated 0.62 (0.45–0.85, p = 0.003) with malignancy, whereas serum LDH 1.02 (1.0–1.03, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 25 publications
9
80
5
Order By: Relevance
“…Similar to other studies we found that larger amount of fluid drained, higher pleural fluid protein and higher pleural fluid LDH were associated with a higher risk of MPE [28]. LDH is found in numerous clinical conditions and had been reported as a marker of poor outcome in cancer patients [29].…”
Section: Discussionsupporting
confidence: 79%
“…Similar to other studies we found that larger amount of fluid drained, higher pleural fluid protein and higher pleural fluid LDH were associated with a higher risk of MPE [28]. LDH is found in numerous clinical conditions and had been reported as a marker of poor outcome in cancer patients [29].…”
Section: Discussionsupporting
confidence: 79%
“…These findings were slightly lower than the previous results of our retrospective study on cancer ratio where this cut-off level allowed distinction of MPE from nonmalignant pleural effusion with the sensitivity and specificity of 0.98 and 0.94 and PLR and NLR of 32.6 and 0.03, respectively [11]. …”
Section: Discussioncontrasting
confidence: 76%
“…We calculated and analysed three ratios:The ratio between serum LDH and pleural ADA: this was called “cancer ratio” as per our previous publication [11]. This was calculated for prospective validation of our previous retrospectively published findings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cases, though, ADA levels in pleural fluid were low and rather ineffective in the initial diagnostic assessment of our patients. On the other hand, in a recently published study the cancer ratio (serum LDH/pleural ADA ratio) (36) has been evaluated in diagnosing MPE, with sensitivity and specificity also in 90s. Nevertheless, further studies are warranted.…”
Section: Discussionmentioning
confidence: 99%